2013
DOI: 10.3389/fnhum.2013.00847
|View full text |Cite
|
Sign up to set email alerts
|

Is synesthesia more common in patients with Asperger syndrome?

Abstract: There is increasing evidence from case reports that synesthesia is more common in individuals with autism spectrum conditions (ASC). Further, genes related to synesthesia have also been found to be linked to ASC and, similar to synaesthetes, individuals with ASC show altered brain connectivity and unusual brain activation during sensory processing. However, up to now a systematic investigation of whether synesthesia is more common in ASC patients is missing. The aim of the current pilot study was to test this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 62 publications
4
63
0
11
Order By: Relevance
“…However, these findings have been replicated in a second study (Neufeld et al, 2013) that showed elevated rates of synaesthesia in people with ASC using both self-report and an objective test for synaesthesia. Neufeld et al screened 29 individuals with Asperger Syndrome for grapheme-colour synaesthesia using a validated test of genuineness (described below).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…However, these findings have been replicated in a second study (Neufeld et al, 2013) that showed elevated rates of synaesthesia in people with ASC using both self-report and an objective test for synaesthesia. Neufeld et al screened 29 individuals with Asperger Syndrome for grapheme-colour synaesthesia using a validated test of genuineness (described below).…”
Section: Introductionmentioning
confidence: 66%
“…Our current study aims to further understand the association between synaesthesia, ASC, and savant syndrome by asking whether synaesthesia is related to ASC in general, as has been suggested by Baron-Cohen et al (2013) and Neufeld et al (2013), or whether this relationship is more specifically linked to the presence of savant skills. To answer this question, we recruited three groups of individuals: individuals diagnosed with ASC who also report having a prodigious savant skill (henceforth 'ASC-savants'); individuals diagnosed with ASC but without an accompanying savant skill (henceforth 'ASC-non-savants'); and 'controls' who have neither a diagnosis of ASC nor a reported savant skill.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then we also have Baron-Cohen et al (2013) and Neufeld et al (2013), who raise the question of the extent of synesthesia amongst those on the autistic spectrum, proposing that the synesthesia in this group might be, in effect, a spandrel of the more broad-scale hyper-connectivity resulting in autism. And the topic of hyper-connectivity then may lead us back to such items as Gregersen et al's (2013) recent study, further exploring the similarities between absolute pitch as certain forms of synesthesia, a topic also being explored by Zamm et al (2013).…”
Section: What Is Insidementioning
confidence: 99%